Experimental investigation of the effect of temperature on the density of kaolin clay. (2021) - Abubakar, M.; Muthuraja, A.; Ahmad, N.
Abstract: In this study, natural clay mineral was investigated to understand the influence of temperature on its physical properties. To explore the potential suitability of clay as raw material for various high temperature applications, investigation of chemical composition analysis of the clay was conducted using X-ray fluorescence (XRF). The characteristics of the fired ceramics were assessed and the results revealed the presence of alumina, silica and potassium oxide in significant level than other impurities in the clay. Due to superior bonding behaviour at elevated temperatures, it was obtained that the bulk density increases sharply at firing temperatures above 1100 °C. The result revealed that the increase in linear shrinkage with firing temperature due to the liquid phase formation at firing temperature above 1000 °C and the highest linear shrinkage is achieved at firing temperature of 1200 °C. It was also revealed that the shrinkage and bulk density directly proportional to each other. From the maturation results, the ceramic properties such as bulk density and shrinkage increases with temperature, however, the apparent porosity decreases with temperature. The characterization test was carried out as per the standards and High Temperature furnace was used for firing the clay materials.